El principio tomista «gratia non tollit naturam, sed perficit eam» y su aplicación a la actividad de la psicología y la terapia psicológica - Andereggen, Ignacio Eugenio María (Sapientia, 2017)
We begin from a very important part of St. Thomas Aquinas work Summa Theologiae I-II. For Aquinas, following , one cannot fully meet the human natural order without the grace, apart from perfection it delivers. After briefly seeing some parallel topics, and Augustinian and Thomist teaching of the Council of Trent, we consider what is meant by psychotherapy and psychology and its distinction from psychiatry. Here we proceed to a consideration from the spiritual theology, as an inadequate knowledge of the laws of spiritual evolution produces the “necessity” of psychotherapy. We go then to the relationship between teaching and psychology, and the need for a renewal of Thomist bases. We end by mentioning some practical problems: education, individual crisis, church environments.